Dampak Pemberian Apresiasi terhadap Motivasi Belajar Siswa Kelas II SD 07 Marisa - Muh. Wahyuddin S. Adam; Riyanti Ismail; Sasri Ali; Ana Sisilia (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
The Impact of Giving Appreciation on Learning Motivation Giving appreciation is an effective way to increase student learning motivation. Appreciation can be in the form of praise, awards, or recognition for the efforts and achievements achieved. When students receive appreciation, they tend to feel valued, motivated to learn better, and confident in developing their potential. Appreciation also has a positive impact on the learning atmosphere. Students who feel appreciated usually show higher involvement in the learning process, have a positive attitude towards learning, and are more persistent in facing challenges. Apart from that, giving appreciation can strengthen the relationship between educators and students, creating an environment that is supportive and conducive to learning. However, it is important for educators to give appreciation proportionally and sincerely. Excessive or inappropriate appreciation for student efforts can actually reduce their effectiveness. Therefore, appreciation must be given by considering students' efforts, processes and achievements objectively. Overall, giving appropriate appreciation can be an important strategy in building sustainable learning motivation and supporting students' academic and personal development.